New aspects of axonal structure and function - Feldmeyer, Dirk. (Springer US :, 2010)
For any neuronal cell type, axons are unique neuronal output elements that display very heterogeneous patterns with respect to shape, length, and target structure. New Aspects of Axonal Structure and Function summarizes recent findings covering morphological, physiological, developmental, computational, and pathophysiological aspects of axons. The book covers new findings concerning axonal structure and functions together with their implications for signal transduction in the nervous system. The book also describes the processes implicated in the formation of axonal arbors and the transport of subcellular elements to their targets. Finally, New Aspects of Axonal Structure and Function also shows how a dysfunction in one or several of these steps could lead to axonal degeneration and ultimately to neurodegenerative diseases. New Aspects of Axonal Structure and Function can be used as a reference for neuroscientists, neurophysiologists, neuroanatomists, computational neuroscientists, cellular neuroscientists, as well as Ph.D. students in various neuroscience programs. About the Editors: Dirk Feldmeyer was born in Dortmund, Germany and studied Biology and German literature and linguistics at the Ruhr-University in Bochum where he received his Ph.D. in 1987. In 2001, he obtained a postdoctoral fellowship in the Dept. of Pharmacology, University College London. He joined the Dept. of Cell Physiology, at the Max Planck Institute of Medical Research in 1995 and in 2004 became independent group leader at the Institute of Medicine, Research Centre Jülich. In 2008 he was appointed to a professorship on "Function of Cortical Microcircuits" in the Dept. of Psychiatry and Psychotherapy, RWTH Aachen University, Germany. His research interests are neuronal microcircuits in the neocortex, their development and modulation. Joachim H.R. Lübke was born on November 4, 1956 in Gelsenkirchen and trained as a biological-technical assistant. He studied biology at the Georg-Auversity of Göttingen and did his Ph.D. at the Max Planck Institute for Biophysical Chemistry (Head: Prof. Otto-Detlev Creutzfeld). From 1991-1993 he was a postdoctoral fellow of the Royal Society at the Dept. of Human Anatomy (Head: Prof. Ray Guillery) of the University of Oxford. From there he moved as a "von Helmholtz" fellow of the German ministry of Eduction and Research to the Institute of Anatomy at the Albert-Ludwigs University Freiburg (Head: Prof. Michael Frotscher). In 1997 he received the Wolfgang-Bargmann prize of the German Anatomical Society. He did his "habilitation" in anatomy and neuroanatomy in 1999 and was appointed assistant professor at the Department of Anatomy of the University of Freiburg in 2000. In 2003 he was appointed to group leader position at the Institute of Medicine, Research Centre Jülich. He was appointed professor at the Faculty of Medicine of the Heinrich-Heine-University Düsseldorf. In 2008 he was also appointed to a Professorship on "Structure of Cortical Functional Units" at the Dept. of Psychiatry and Psychotherapy, RWTH Aachen University, Germany. Axons in Development -- Molecular Aspects of Commissural Axon Guidance -- Subplate and the Formation of the Earliest Cerebral Cortical Circuits -- Axonal Function -- Sodium Signals and Their Significance for Axonal Function -- New Insights in Information Processing in the Axon -- Electrical Coupling of Axons -- To Myelinate or Not to Myelinate? -- Axons and Neuronal Circuits -- An Axonal Perspective on Cortical Circuits -- Axons Predict Neuronal Connectivity Within and Between Cortical Columns and Serve as Primary Classifiers of Interneurons in a Cortical Column -- The Axon of Excitatory Neurons in the Neocortex: Projection Patterns and Target Specificity -- Axons and Degeneration/Regeneration -- Axon Degeneration: Mechanisms and Consequences -- Regeneration After CNS Lesion: Help from the Immune System?.